Strategi Penguatan Pendidikan Karakter Didalam Meningkatkan Semangat Belajar Anak-Anak Panti - Claudia Purba, Geby; Putra Kasea Sinaga, Randa (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
Character is the psychological traits, morals, character and disposition that differentiate a person from others. Character education is related to the social structural dimension to create a social system that is conducive to individual growth. Character formation requires a relatively long and continuous process. The strategy to strengthen character education is carried out through attitudes, namely: example, enforcing discipline and habituation. It is necessary to instill in the children of the orphanage the strengthening of character education in increasing the enthusiasm for learning of the children of the orphanage so that there is an interest in reading books. This means that the children of the orphanage always do the homework given by the teacher and can appreciate the time in terms of studying. The problem solving process was carried out in the PKL II mini project activity using the group work method at the mezzo intervention level. The stages used are the general stages (General Method) as follows: Engagement, Intake & Contract, Assessment, Planning, Intervention, Evaluation and Termination. What is the focus of the client's problem solving process is their lack of interest in reading books and rarely doing the homework given by the teacher and their lack of respect for time when it comes to studying. The aim of the program has been achieved, as evidenced by the client always diligently reading books every night and always doing the homework given by the teacher and being able to respect time when it comes to studying.